A multimethods randomized trial found that plain language versions improved adults understanding of health recommendations - Sayfi, Shahab; Charide, Rana; Elliott, Sarah A; Hartling, Lisa; Munan, Matthew; Stallwood, Lisa; Butcher, Nancy J; Richards, Dawn P; Mathew, Joseph L; Suvada, Jozef; Akl, Elie A; Kredo, Tamara; et al. (Journal of clinical epidemiology, 2024)
OBJECTIVES: To make informed decisions, the general population should have access to accessible and understandable health recommendations. To compare understanding, accessibility, usability, satisfaction, intention to implement, and preference of adults provided with a digital "Plain Language Recommendation" (PLR) format vs. the original "Standard Language Version" (SLV). STUDY DESIGN AND SETTING: An allocation-concealed, blinded, controlled superiority trial and a qualitative study to understand participant preferences. An international on-line survey. 488 adults with some English proficiency. 67.8% of participants identified as female, 62.3% were from the Americas, 70.1% identified as white, 32.2% had a bachelor's degree as their highest completed education, and 42% said they were very comfortable reading health information. In collaboration with patient partners, advisors, and the Cochrane Consumer Network, we developed a plain language format of guideline recommendations (PLRs) to compare their effectiveness vs. the original standard language versions (SLVs) as published in the source guideline. We selected two recommendations about COVID-19 vaccine, similar in their content, to compare our versions, one from the World Health Organization (WHO) and one from Centers for Disease Control and Prevention (CDC). The primary outcome was understanding, measured as the proportion of correct responses to seven comprehension questions. Secondary outcomes were accessibility, usability, satisfaction, preference, and intended behavior, measured on a 1-7 scale. RESULTS: Participants randomized to the PLR group had a higher proportion of correct responses to the understanding questions for the WHO recommendation (mean difference [MD] of 19.8%, 95% confidence interval [CI] 14.7-24.9%; P < 0.001) but this difference was smaller and not statistically significant for the CDC recommendation (MD of 3.9%, 95% CI -0.7% to 8.3%; P = 0.096). However, regardless of the recommendation, participants found the PLRs more accessible, (MD of 1.2 on the seven-point scale, 95% CI 0.9-1.4%; P < 0.001) and more satisfying (MD of 1.2, 95% CI 0.9-1.4%; P < 0.001). They were also more likely to follow the recommendation if they had not already followed it (MD of 1.2, 95% CI 0.7-1.8%; P < 0.001) and share it with other people they know (MD of 1.9, 95% CI 0.5-1.2%; P < 0.001). There was no significant difference in the preference between the two formats (MD of -0.3, 95% CI -0.5% to 0.03%; P = 0.078). The qualitative interviews supported and contextualized these findings. CONCLUSION: Health information provided in a PLR format improved understanding, accessibility, usability, and satisfaction and thereby has the potential to shape public decision-making behavior.
Keywords: jazyk (prostředek komunikace); COVID-19 Vaccines; vakcíny proti COVID-19; vzdělávání pacientů jako téma; Consumer Health Information; United States; mužské pohlaví; Adult; Health Knowledge, Attitudes, Practice; pochopení; ženské pohlaví; Humans; Spojené státy americké; Patient Education as Topic; Language; dospělí; zdraví - znalosti, postoje, praxe; informace pro uživatele zdravotní péče; Female; Comprehension; lidé; Male